Metal Organic Frameworks (MOFs) as efficient carrier for targeted nanodrug delivery - Karki, Ravi; Adhikari, Dipak; Adhikari, Kapil; Pantha, Nurapati (Himalayan Physics, 2020)
A controllable and targeted drug delivery system development is imperative and important to reduce side effects and enhance the therapeutic efficacy of drugs. Metal-organic frameworks (MOFs), an emerging type of hybrid porous materials synthesized from metal ions or clusters abridged by organic linkers. They have attracted increasing attention in the recent years owing to the unique physical structures possessed, and the potential for wide range of applications. The superior properties of MOFs, such as well-deﬁned pore aperture, tailorable composition and structure, tunable size, versatile functionality, high agent loading, and improved biocompatibility, have made them promising candidates as drug delivery hosts. MOFs for drug encapsulation and delivery is of great interest and many very promising results have been found, indicating that these porous solids exhibit several advantages over existing systems. This review highlights the recent advances in the synthesis, functionalization, and applications of MOFs in nanodrug delivery, and has classiﬁed them using drug loading strategies.